Anti-Diabetics Drug Usage and Related Pharmaceutical Care Issues among Geriatrics and Non-Geriatrics: A Comparative Assessment - Inamdar, Syed Zia; Kulkarni, Raghavendra Vinayakarao (Indian Journal of Pharmacy Practice)
Background and Introduction: Diabetes Mellitus presents a challenge and continues to be a focus of medical care as population continues to age and live longer. The treatment approach in elderly and younger patients is influenced by ageing, life expectancy; co morbidities and severity of the vascular complications which increases the risk for development of pharmaceutical care issues. The present study evaluates anti-diabetic medication use and related pharmaceutical care issues among geriatric and non-geriatric population. Methods: A longitudinal cohort study was conducted in patients admitted to tertiary care hospital in north Karnataka with type 2 diabetes mellitus of age 18 years and above. Patient’s demographic, clinical characteristics and anti-diabetic medications were reviewed to detect and report any pharmaceutical care issue using Pharmaceutical Care Network Europe checklist. Beers criteria were also utilized for geriatrics assessment. Results: A total of 230 diabetic [geriatric 53.48% and non-geriatric 46.52%] patients were finally assessed for the study. Of the total drugs prescribed, anti-diabetic drugs category shared around 25.74% [geriatrics 15.26% and 10.48% in non-geriatrics]. A total of 147 pharmaceutical care issue related to anti diabetics were reported [69.38% in geriatrics and 30.61% in non-geriatrics], which are related to; drug not appropriate for therapy [geriatrics 35.29% non-geriatrics 22.22], Contraindications related [geriatrics 26.47% non geriatrics 17.77%], adverse drug reactions [geriatrics 6.86% non-geriatrics 6.66%] and drug interaction [geriatrics 23.53% non-geriatrics 20%]. Discussion: The geriatric population’s social factors, thoughts and behavioral patterns, old age and concomitant diseases obscure diabetes management and contribute for the increased frequency of pharmaceutical care issues compare to non-geriatrics. Conclusion: The study shows a higher incidence of pharmaceutical care issues in geriatrics compare to nongeriatrics. The treatment plan for diabetes in geriatrics is not dissimilar to that of non-geriatrics. An individualized glycemic goals and interdisciplinary care is the key for optimal management of diabetes in different age groups.
Keywords: Geriatric; Non-geriatric; Anti diabetic agents; Pharmaceutical care issues